Food Safety on the Farm: Good Agricultural Practices and Good Handling Practices – Packing Facility Sanitation - Alexandra Chang; Renée M. Goodrich-Schneider; Keith R. Schneider (EDIS, 2012)
This is part of the Food Safety on the Farm series, a collection that reviews the generally recognized principles of GAPs as they relate to produce, primarily at the farm level and with a particular focus on fresh Florida crops and practices. This publication focuses on GAPs and GHPs relating specifically to packing operation sanitation. Written by Keith R. Schneider, Renée M. Goodrich-Schneider, and Alexandra Chang, and published by the UF Department of Food Science and Human Nutrition, March 2012.